Parceria trans-pacífico: Um acordo megarregional na fronteira da regulaç\~ao do comércio internacional? - Flavio Lyrio Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The aim of the article is to draw an overview of the Trans-Pacific Partnership Agreement (TPP), analyzing its formation and the main issues that will probably be part of the future agreement, and evaluating the perspectives for its conclusion and possible impacts, with special focus upon developing countries which are outside the deal, such as Brazil. The TPP aims to be a "XXIst century agreement", covering not only market access for goods, services and investment, but also a new set of disciplines ranging from regulatory convergence and harmonization of technical standards to labor principles and measures for environmental conservation. Nevertheless, the heterogeneity that characterizes the members of the initiative, as well as the multiplicity and complexity of issues, many of them still absent of the multilateral framework, raises questions about the possibility of successful negotiations, as well as on the features of the final agreement. If successful, however, its effects will probably be of considerable magnitude. Depending on the degree of success in areas such as regulatory harmonization and rules of origin, it is possible that the TPP will work as an incentive to companies to turn their activities towards the block, deepening the regionalization of global value chains. The agreement can also have deep effects on the functioning of the multilateral trading system itself, should it weaken the role of the WTO main locus of rule-making on international trade, which may be particularly harmful to Brazil, outside not only of TPP but of all mega-regional initiatives.
Keywords: F13; F15; 330; trans-pacific partnership; mega-regional negotiations; trade agreements